Analisis Kesalahan Mahasiswa Dalam Menafsirkan Implikatur Percakapan Pada Teks Dialog Konteporer Dan Implikasinya Bagi Pembelajaran Pragmatik - Harianja, Anjelina Septiana; Putrayasa, Ida Bagus; Alfin, Yunita Ratna; Dewi, Ni Putu Eva Fransiska; Susila, Luh Putu Adhi Laksmini; Suandi, I Nengah; Paramartha, I Ketut (Universitas Pakuan, 2026)
ANALYSIS OF STUDENTS' ERRORS IN INTERPRETING CONVERSATIONAL IMPLICATIONS IN CONTEMPORARY DIALOGUE TEXTS AND ITS IMPLICATIONS FOR PRAGMATIC LEARNING Abstract. This study aims to identify and analyze in depth the types of errors made by Indonesian Language Education students in interpreting conversational implicatures in contemporary dialogues. Implicature, as an implied meaning arising from the violation of Grice's Cooperative Principle, is not merely a theoretical concept, but a crucial competency that determines the success of authentic communication and is a primary prerequisite for prospective effective language teachers. Using a qualitative descriptive method, data were collected through the Conversational Implicature Interpretation Test (T-IIP) taken by 60 sixth-semester students. This test, consisting of 20 authentic dialogue items from social media, films, and interviews, was designed not only to measure interpretation skills, but also students' ability to identify violated maxims and provide contextual justification for their interpretations. The results showed a significant level of interpretation errors, amounting to 48.75% of the total 1,200 responses. The most dominant type of error occurred in the interpretation of the Maxim of Quality (58.33%), especially in irony and sarcasm, followed by errors in the Maxim of Relevance (55.00%). The root of these errors lies in a lack of contextual awareness (socio-pragmatic awareness) and a shallow understanding of pragmatic inference processes. The implications of these findings serve as a strong call for a reformulation of pragmatics learning, emphasizing the need for a paradigm shift from decontextualized theoretical approaches to authentic case-based analysis that focuses on sociopragmatic contexts, integrating contemporary dialogue and cooperative learning models to enhance students' pragmatic awareness. Keywords: Error Analysis, Conversational Implicature, Grice's Cooperative Principle, Contemporary Dialogue, Pragmatic Learning